(3JQGLe QhGI CMGOjK cJGH GdeUGHjM ddHZhis - (3CHh GdhaG eMeO Hf YHO Gddg Hf eMeO GdHNTjs
(3ChdgG (B:s
(3GdMeO ddg TQa fbdI GdMOjK hLYdge CFeI jgOhf HCeQg ai GdbOje hGdMOjK GdN s
(3BNQgG (B:s
(3hCdeY HfhQg eMjGg ef GdSjQI GdeMeOjI ddfGS ef GdgOGjI GdCMeOjI eG jZfjge Yf GdJdhjM , hCMSf Gddg SHMGfg dg HMSf GdNJGe HLGg eMeO NGJe GdQSd GdcQGe GdN s
(3hGdjcQhajde Hg Jda HSjWs
(3JHUQI GdYfhGf (B:s
(3LeY s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B38 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs